Ensuring Data Accuracy and Compliance in Remote Healthcare Monitoring - Sharath Akula (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Remote healthcare delivery and clinical trials have undergone a dramatic transformation, necessitating robust frameworks for ensuring data accuracy and regulatory compliance in virtual settings. This comprehensive article explores the intricate challenges healthcare organizations face when implementing remote monitoring systems while maintaining data integrity and adhering to stringent regulatory requirements. Through examination of current technological infrastructure, quality control methodologies, and regulatory frameworks, this article presents a structured approach to achieving reliable data collection in remote care environments. The article addresses critical aspects, including device validation protocols, HIPAA compliance in virtual settings, and standardized procedures for remote patient monitoring, while offering practical solutions for common challenges in technology adoption and data discrepancy management. This article indicates that the successful implementation of remote healthcare data systems requires a three-pronged approach: robust technical infrastructure, comprehensive staff training programs, and patient-centric education initiatives. Furthermore, this article identifies emerging trends in artificial intelligence and predictive analytics that promise to enhance data validation processes and compliance monitoring in remote healthcare settings. This article provides healthcare professionals and organizations with actionable insights for establishing and maintaining reliable remote data collection systems while ensuring regulatory compliance and optimal patient care outcomes.